Production of pristine, sulfur-coated and silicon-alloyed germanium nanoparticles via laser pyrolysis. (8th July 2015) - Kim, Seongbeom; Yi Park, Song; Jeong, Jaeki; Kim, Gi-Hwan; Rohani, Parham; Suk Kim, Dong; Swihart, Mark T; Young Kim, Jin
Abstract: Here we demonstrate production of three types of germanium containing nanoparticles (NPs) by laser pyrolysis of GeH4 and characterize their sizes, structures and composition. Pristine Ge NPs were fabricated with 50 standard cubic centimeter per minute (sccm) of GeH4 and 25 sccm of SF6 as a photosensitizer gas, while sulfur-coated Ge NPs were produced with 25 sccm of GeH4 and 50 sccm of SF6 . The laser pyrolysis of SiH4 /GeH4 mixtures produced Si1− x Ge x alloy NPs. Effects of key process parameters including laser intensity and gas flow rates on NP properties have been investigated. The ability of the laser pyrolysis technique to flexibly produce a variety of germanium-containing NPs, as illustrated in this study shows promise for commercial-scale production of new nanomaterials as high purity dry powders.